2022
DOI: 10.1186/s13073-022-01013-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale CRISPR screens identify host factors that promote human coronavirus infection

Abstract: Background The COVID-19 pandemic has resulted in 275 million infections and 5.4 million deaths as of December 2021. While effective vaccines are being administered globally, there is still a great need for antiviral therapies as antigenically novel SARS-CoV-2 variants continue to emerge across the globe. Viruses require host factors at every step in their life cycle, representing a rich pool of candidate targets for antiviral drug design. Methods T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…However, our findings that endogenous IFITM expression is critical for efficient replication of genuine SARS-CoV-2 in human lung and gut cells ( 4 ) are not contradicted by experimental evidence since inhibitory effects of IFITMs were generally observed under more artificial conditions. Notably, our results are in line with the recent identification of IFITM proteins as SARS-CoV-2 dependency factors in Vero E6 cells ( 52 ). It has been previously shown that IFITMs promote infection by human coronavirus OC43 ( 10 ), and recent data suggest that IFITM1 and -3 promote infection by herpesviruses and hepatitis B and D viruses ( 53 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings that endogenous IFITM expression is critical for efficient replication of genuine SARS-CoV-2 in human lung and gut cells ( 4 ) are not contradicted by experimental evidence since inhibitory effects of IFITMs were generally observed under more artificial conditions. Notably, our results are in line with the recent identification of IFITM proteins as SARS-CoV-2 dependency factors in Vero E6 cells ( 52 ). It has been previously shown that IFITMs promote infection by human coronavirus OC43 ( 10 ), and recent data suggest that IFITM1 and -3 promote infection by herpesviruses and hepatitis B and D viruses ( 53 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, one study recently screened a number of drugs in vitro against human coronaviruses, including an inhibitor of FGFR1-3 approved for various lung disease indications such as idiopathic pulmonary fibrosis, which showed only “moderate” inhibition of SARS-CoV-2 cytotoxicity 29 . However, we do not draw conclusions either way from this result, as the mechanism of action to address acute infection may be different from the mechanism of action needed to address post-acute symptoms (as in the case of NRP1, above).…”
Section: Discussionmentioning
confidence: 99%
“…The three above-described genes may be implicated in vesicle formation during autophagy. Grodzki et al ( 165 ) also identified TMEM41B and RAB7A . They demonstrated that CCZ1 and EDC4 were required for SARS-CoV-2 and HCoV-OC43 infection in CCZ1 or EDC4 knockdown cells.…”
Section: High-throughput Screening Identification Of Host Cell Factor...mentioning
confidence: 97%